2020
DOI: 10.1111/jcmm.15860
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cell–secreted extracellular vesicles carrying TGF‐β1 up‐regulate miR‐132 and promote mouse M2 macrophage polarization

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 38 publications
1
20
0
Order By: Relevance
“…Resting MSCs release exosomes and MVs with positivity for the characteristic markers of these cells (CD105, CD90, and CD73) and the absence of MHC-I, MHC-II, CD34, and CD45 [48,[90][91][92][93][94]122,123]; they also transport immunoregulatory molecules such as PD-L1, Gal-1, and TGF-β [90,124] (Figure 3).…”
Section: Immunoregulation Mediated By Extracellular Vesiclesmentioning
confidence: 99%
“…Resting MSCs release exosomes and MVs with positivity for the characteristic markers of these cells (CD105, CD90, and CD73) and the absence of MHC-I, MHC-II, CD34, and CD45 [48,[90][91][92][93][94]122,123]; they also transport immunoregulatory molecules such as PD-L1, Gal-1, and TGF-β [90,124] (Figure 3).…”
Section: Immunoregulation Mediated By Extracellular Vesiclesmentioning
confidence: 99%
“…These effects can be explained in part through microRNA, as microRNAs such as miR-132 are highly upregulated during inflammation and can induce M2 polarization through regulation of TLRs [285][286][287]. Studies have found that miR-132 located within MSC-Exos can elevate IL-10 expression and decrease levels of NF-кB, IL-6 and IL-1β in favor of inflammation resolution [288][289][290]. Broadly, exosomes have shown significant beneficial effects on proliferation, collagen deposition, and angiogenesis, even in states of chronic wounds and comorbidities such as diabetes [272,273,291].…”
Section: Wound Healingmentioning
confidence: 99%
“…Several studies suggest a key role of PGE2, as the inhibition of PGE2 or the cyclooxygenase-2 (COX2) pathway abrogated the observed inhibitory effects ( Németh et al, 2009 ; Jin et al, 2019 ; Ortiz-Virumbrales et al, 2020 ). Previous studies using AD- or BM-MSCs indicated that the paracrine action is partially mediated by exosomes ( Biswas et al, 2019 ; Cho et al, 2019 ; He et al, 2019 ; Liu et al, 2019b ; Wang et al, 2020b ). The exosomes contained TGF-β, C1q, semaphorins, and micro (mi) RNAs, regulating the macrophage polarization and inducing overexpression of programmed cell death 1 ligand 1 (PD-L1).…”
Section: Modulation Of Innate Immunity By Mscsmentioning
confidence: 99%